ALGORITHM OF DECISION MAKING IN RISK CONDITIONS IN LARGE SYSTEMS - Kovalyuk , D. O.; Moskvina , S. M. (Problems of Informatization and Management, 2021)
The problem of decision-making in conditions of risk is considered. The analysis of existing methods of decision-making in the conditions of risk is carried out, special attention is paid to logical-probabilistic models of risk. A method and algorithm for decision-making based on logical-probabilistic models to be used to control the operation of the lime kiln are proposed.